Efficiency Versus Emotion: Analyzing the Tug-of-War Between Rationality and Behavioral Biases in Financial Markets - Muslim, Muslim (Advances in Economics & Financial Studies, 2023)
The purpose of this study is to examine the interplay between market efficiency theories and behavioral biases in financial markets, exploring their implications for investment strategies, risk management practices, and regulatory policies. The research design encompasses a comprehensive literature review of efficiency theories, such as the Efficient Market Hypothesis (EMH), and behavioral finance principles, including Prospect Theory and cognitive biases. Empirical evidence from studies by Barberis and Thaler (2003) and others is synthesized to elucidate the prevalence and impact of behavioral biases on investor decisions and market dynamics. Findings reveal systematic deviations from rationality, such as overconfidence, herding behavior, and loss aversion, challenging the assumptions of market efficiency. The discussion highlights the need to integrate behavioral insights into financial models and decision-making processes to enhance market efficiency and investor welfare. Implications include the importance of tailored strategies to mitigate behavioral biases, investor education initiatives, and regulatory interventions to promote market integrity and protect investors. Overall, this study underscores the dynamic nature of financial markets and the critical role of behavioral finance in shaping their evolution and resilience.